Copper,zinc superoxide dismutase is primarily a cytosolic protein in human cells. - Crapo, J D (1992)
The intracellular localization of human copper,zinc superoxide dismutase (Cu,Zn-SOD; superoxide:superoxide oxidoreductase, EC 1.15.1.1) was evaluated by using EM immunocytochemistry and both isolated human cell lines and human tissues. Eight monoclonal antibodies raised against either native or recombinant human Cu,Zn-SOD and two polyclonal antibodies raised against either native or recombinant human Cu,Zn-SOD were used. Fixation with 2% paraformaldehyde/0.2% glutaraldehyde was found necessary to preserve normal distribution of the protein. Monoclonal antibodies were less effective than polyclonal antibodies in recognizing the antigen after adequate fixation of tissue. Cu,Zn-SOD was found widely distributed in the cell cytosol and in the cell nucleus, consistent with it being a soluble cytosolic protein. Mitochondria and secretory compartments did not label for this protein. In human cells, peroxisomes showed a labeling density slightly less than that of cytoplasm.